Acute Malignant Transformation as A Rare Complication of Middle Cerebral Artery Infarction - Annisa Bunga Nafara; Ika Yulieta Margaretha Permatasari (Magna Neurologica, 2026)
Background: Malignant ischemic stroke is a stroke characterized by extensive acute edema resulting in a space-occupying lesion. This transformation occurs in 10% of ischemic strokes with a mortality rate up to 80%. Hence, it is crucial to early detection and timely treatment. Case: A 51-year-old male was diagnosed with ischemic stroke, presented with NIHSS 11 and ASPECTS 4. Within 26 hours, the patient's level of consciousness declined progressively from a GCS of 15 to a GCS of 10. Serial brain imaging using CT scan and MRI revealed infarct expansion, a space-occupying lesion, and further midline shift. During decompressive craniectomy, extensive edema was found without hemorrhage, suggesting malignant ischemic stroke. After 6 months, the patient had undergone cranioplasty, with no significant complaints, but left hemiparesis remained. Discussion: Malignant ischemic stroke occurs within 5 days after onset. Diagnosis of malignant complication should be considered in ischemic stroke patients with younger age, higher NIHSS, not receiving thrombolysis, neurological status decline in 4-6 hours after onset, wide hypoattenuation in MCA territory, and signs of progressive space-occupying lesion in brain imaging. Management of malignant ischemic stroke consists of managing intracranial pressure with pharmacology and decompressive craniectomy. Conclusion: Malignant transformation is a rare complication of ischemic stroke. Early and accurate diagnosis is crucial to determine the prognosis. Pharmacological therapy and decompressive craniectomy surgery are considered life-saving therapies, but are not able to reduce morbidity in the patient.